Study of Optical Properties of Chalcogenide Metal Thin Films by Means of UV-Visible Spectrophotometer: A Review - Ho, Soon Min (IDOSI Publications, 2016)
In this work, UV-visible spectrophotometer was used to investigate the band gap energy and optical properties of obtained thin films prepared by using various deposition methods in the range of 200 to 800 nm. This tool was selected due to its quick analysis ability and easy to use by many researchers. Nowadays, thin films characterization technology is in high demand in all engineering and material science areas. This is because of the properties of thin films can vary dramatically under various deposition conditions.